LIABILITY OF ONLINE PLATFORMS FOR CONTENT MODERATION FROM THE PERSPECTIVE OF THE EUROPEAN COURT OF HUMAN RIGHTS – CHALLENGES AND RECENT DEVELOPMENTS - Marijana Mladenov; Tamara Staparski
While not a novel phenomenon, online platforms have gained significant economic and societal importance over the past decade, and the public discourse around their responsibilities and liabilities has reached an exceptional level. Online platforms significantly contribute to facilitating the exchange and access to information, enabling the widespread distribution of all types of content, regardless of their legality. The regulation of content on online platforms undoubtedly impacts the protection of human rights, particularly freedom of expression, which has led the European Court of Human Rights (ECtHR) to establish important criteria through its jurisprudence. To understand the implications of the ECtHR’s case law, it is important to briefly present the concept of platform liability within the European legal framework, which is outlined in the opening section of the paper. In the subsequent part, the authors analyze the relevant ECtHR jurisprudence. The aim of the paper is to clarify the main standards of the ECtHR’s approach to the human rights implications of online platforms’ liability for content moderation, while also potentially highlighting their limitations.